Can home videos made on smartphones complement video-EEG in diagnosing psychogenic nonepileptic seizures?. (November 2018) - Ramanujam, Bhargavi; Dash, Deepa; Tripathi, Manjari
Highlights: Home videos on smart phones can diagnose PNES early in those awaiting video-EEG. Smart-phone home videos differentiated PNES from epileptic seizures in 97% cases. Home videos had sensitivity of 95%, specificity of 97% for PNES, gold standard- video-EEG. Most common semiological feature pointing towards PNES is eye closure. Abstract: Purpose: To assess the contribution home-videos made on mobile phones can make to the diagnosis of Psychogenic Nonepileptic Seizures (PNES). Methods: Consecutive patients 10–50 years old, with episodes of altered behavior or abnormal movements, unresponsiveness, or falls, were recruited after they had obtained 'good' or 'fair' quality (quality of video scale (QOV)) home-videos of their episodes on personal mobile phones; these subjects underwent video-electroencephalography (VEEG). Diagnoses of PNES, other physiological events or epileptic seizure (ES) on home-videos (by the epilepsy fellow, step 1) and on VEEGs (by a fully trained epileptologist unaware of the home-video recording, step 2) were compared. Results: We screened 783 patients, and finally analyzed 269; 155 subjects had `fair' (QOV 5–7) and 114 had 'good'(QOV 8–10) quality home-videos. Concordance between steps 1 and 2 was seen in 261 of 269 (97.2%) subjects, and no significant difference was noted between the two modalities in diagnosing PNES. Differentiation between PNES, ES and other physiological events using home-videos was correct in 49.1% subjects if 532 (all subjects asked to make home-videos) and 70.7% if 369 (subjects with 'good' or 'fair' home videos), were used as denominators. Home-videos diagnosed PNES with the sensitivity of 95.4% (95% CI: 87.2%–99.1%), specificity of 97.5% (95% CI: 94.3%–99.2%), positive and negative predictive values of 92.65% (95% CI: 84.1%–96.8%) and 98.5% (95% CI: 95.6%–99.5%) respectively. Conclusion: Home-videos of good quality can complement VEEG in diagnosing PNES in a cost-effective way and help initiate appropriate management.